2022
DOI: 10.1088/1361-6528/ac4c16
|View full text |Cite
|
Sign up to set email alerts
|

Experiment and simulation of flexible CNT/SA/PDMS electromagnetic shielding composite

Abstract: Flexible electromagnetic shielding composites have a great potential for wide range applications. In this study, two flexible composites were produced by plating Ni nanoparticles on CNTs (Ni@CNT/SA/PDMS composites) or infiltrating CNF/PDMS polymer into CNT/SA sponge skeleton (CNT/SA/CNF/PDMS composites). The electromagnetic interference shielding effectiveness values of the above two composites are almost as twice as that of CNT/SA/PDMS composite at a same CNT loading. Introducing nano-sized Ni particles on CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In regard to numerical simulation, different shielding structures and materials have also been proposed. M. Bajtos et al [ 12 ] proposed a Mu metal cage shielding structure and numerically investigated its shielding performance, obtaining a maximum shielding efficiency of 90%; J. Pang et al [ 13 ] investigated carbon nanotubes (CNTs)/sodium alginate (SA)/ polydimethylsiloxane (PDMS) composite films containing Ni particles by simulation and calculation, and found that the shielding effectiveness can reach 50 dB by optimizing the cladding rate and size of Ni particles; L. Gozzelino et al [ 14 ] examined a MgB 2 bulk cylinder passive magnetic shielding material via simulation and achieved a shielding factor higher than 175 (equal to 44.9 dB shielding efficiency) at 20 K, and the results were reproduced by measurement. Although the shielding effect of single-layer composite materials is high enough, it is still difficult to achieve a magnetic shielding efficiency of more than 100 dB at low-frequency magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…In regard to numerical simulation, different shielding structures and materials have also been proposed. M. Bajtos et al [ 12 ] proposed a Mu metal cage shielding structure and numerically investigated its shielding performance, obtaining a maximum shielding efficiency of 90%; J. Pang et al [ 13 ] investigated carbon nanotubes (CNTs)/sodium alginate (SA)/ polydimethylsiloxane (PDMS) composite films containing Ni particles by simulation and calculation, and found that the shielding effectiveness can reach 50 dB by optimizing the cladding rate and size of Ni particles; L. Gozzelino et al [ 14 ] examined a MgB 2 bulk cylinder passive magnetic shielding material via simulation and achieved a shielding factor higher than 175 (equal to 44.9 dB shielding efficiency) at 20 K, and the results were reproduced by measurement. Although the shielding effect of single-layer composite materials is high enough, it is still difficult to achieve a magnetic shielding efficiency of more than 100 dB at low-frequency magnetic fields.…”
Section: Introductionmentioning
confidence: 99%